'Why do an MPH?' Motivations and intentions of physicians undertaking postgraduate public health training at the University of Cape Town - Virginia E.M. Zweigenthal; Emma Marquez; Leslie London (Taylor & Francis Group, 2016)
Background: Public health (PH) approaches underpin the management and transformation of health systems in low- and middle-income countries. Despite the Master of Public Health (MPH) rarely being a prerequisite for health service employment in South Africa, many physicians pursue MPH qualifications. Objectives: This study identifies their motivations and career intentions and explored MPH programme strengths and gaps in under- and post-graduate PH training. Design: A cross-sectional study using an online questionnaire was completed by physicians graduating with an MPH between 2000 and 2009 and those enrolled in the programme in 2010 at the University of Cape Town. Results: Nearly a quarter of MPH students were physicians. Of the 65 contactable physicians, 48% responded. They were mid-career physicians who wished to obtain research training (55%), who wished to gain broader perspectives on health (32%), and who used the MPH to advance careers (90%) as researchers, policy-makers, or managers. The MPH widened professional opportunities, with 62% changing jobs. They believed that inadequate undergraduate exposure should be remedied by applying PH approaches to clinical problems in community settings, which would increase the attractiveness of postgraduate PH training. Conclusions: The MPH allows physicians to transition from pure clinical to research, policy and/or management work, preparing them to innovate changes for effective health systems, responsive to the health needs of populations. Limited local job options and incentives are important constraining factors. Advocacy for positions requiring qualifications and benchmarking exit competencies of programmes nationally may promote enrolment.